2007
DOI: 10.1128/aem.02061-06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacterial Prey Species and Their Concentration on Growth of the Amoebae Acanthamoeba castellanii and Hartmannella vermiformis

Abstract: Two amoebae were presented with six bacterial prey at a range of concentrations, and the growth parameters of the amoebae were deduced. All but one bacterium (Synechococcus) resulted in a positive growth response, but the gram-positive bacterium Staphylococcus aureus proved to be difficult to digest and the heavily pigmented bacterium Klebsiella ozaenae induced unusual amoebic behavior prior to ingestion.Protozoa are the major predators in microbial food webs (2), but the effects of different groups vary depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 27 publications
(18 reference statements)
4
51
0
Order By: Relevance
“…This is in agreement with the description of an ideal food source for amoebae suggested by Pickup et al [39] i.e ease of intake during phagocytosis/ingestion. Since amoebae appear to be genetically programmed to eat bacteria it is plausible to suggest that V. vermiformis, may be able to control bacterial populations by feeding on newly dividing S. marcescens providing a promising outcome for infection control in dental treatment.…”
Section: Vermiformis Dominates the Duwl Environment [7] And Their supporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with the description of an ideal food source for amoebae suggested by Pickup et al [39] i.e ease of intake during phagocytosis/ingestion. Since amoebae appear to be genetically programmed to eat bacteria it is plausible to suggest that V. vermiformis, may be able to control bacterial populations by feeding on newly dividing S. marcescens providing a promising outcome for infection control in dental treatment.…”
Section: Vermiformis Dominates the Duwl Environment [7] And Their supporting
confidence: 92%
“…However, in this investigation, V. vermiformis also fed on P. aeruginosa (p < 0.05). These results strongly agree with the study conducted by Pickup et al [39], but disagrees with those of Groscop & Brent [19] who suggested that P. aeruginosa was toxic to an unknown species of the genus Hartmannella.…”
Section: Vermiformis Dominates the Duwl Environment [7] And Their supporting
confidence: 77%
See 1 more Smart Citation
“…However, this predator-prey relationship is complex as some bacteria can prevent normal digestive processes within protozoan food vacuoles (Abu Kwaik et al 1998, Strahl et al 2001, whilst others can undergo the full digestive process and emerge apparently unharmed (Schlimme et al 1995, Pickup et al 2007, Dillon & Parry 2009). This latter phenomenon is poorly understood and may be a result of an active response by bacteria, as it is for pathogens (Abu Kwaik et al 1998), or selective or inefficient digestion by protozoa (González et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Hartmannella, an amoeba predators in Figure 5d. Phylogeny of eukaryotic phyla under 11 years oil palm at Naman Park Sibu, Sarawak, Malaysia. microbial food webs (Pickup et al, 2007) was found in oil palm plantations.…”
Section: Eukaryotic Phylogenymentioning
confidence: 99%